A Question of Latitude - Davis, Richard Harding, 1864-1916 (Salt Lake City, UT : Project Gutenberg, 2006)
"A Question of Latitude" by Richard Harding Davis is a novel written during the early 20th century, likely reflecting the period's imperialistic attitudes and social commentary. The book explores themes of corruption, moral dilemmas, and the clash of cultures through the lens of a young muckraker named Everett, who travels to the Congo to report on exploitation and injustice. The story likely addresses critical issues related to colonialism and the human condition amid the complexities of race and power dynamics. The narrative follows Everett, a passionate journalist from Boston, as he sets out to uncover the truths of the Congo under King Leopold's regime. Initially fueled by a sense of purpose and reform, Everett's journey becomes a profound struggle with his moral compass and identity amidst a brutal and chaotic environment. Encountering both corrupt officials and the stark realities of exploitation, he grapples with his ideals and the seductive allure of a woman named Madame Ducret, which further complicates his commitments. Ultimately, Everett's experiences lead him to question the effectiveness of his mission and the very nature of humanity as he confronts the harrowing intersections of civilization and savagery in the Congo. (This is an automatically generated summary.)
Release date is 2006-05-12
Produced by Don Lainson; David Widger
Keywords: Fiction; Short stories